Cause-related marketing, product innovation and extraordinary sustainable leadership: The root towards sustainability - Christofi, Michael; Leonidou, Erasmia; Vrontis, Demetris (My University, 2015)
This article posits a framework that illustrates how the concepts of cause-related marketing, product innovation and extraordinary sustainable leadership are conjoined in order to create a sustainable organisation. The intended contributions are: to accumulate the state of academic research on successful sustainable development within organisations, and; to identify important underdeveloped connections between cause-related marketing, product innovation and extraordinary sustainable leadership on the one hand, with the three-dimensional concept of sustainability on the other hand. Moreover, this manuscript, to our knowledge, appears to be the first of its kind to theoretically examine the dynamics implied by synthesising these, so far, distinct concepts. Within the model explication, we offer a set of research directions designed to enable researchers to further enhance the integration of the aforementioned concepts from both problem-driven theory development as well as theory-driven practice management dimensions.
Keywords: Sustainability; Sustainable leadership; Cause-related marketing; CRM; Leadership; Product innovation